Jaringan Sosial (Social Network) Antar Jantan Monyet Ekor Panjang (Macaca fascicularis) Di Gunung Meru, Padang, Sumatera Barat - Ami Hidayat; Rizaldi Rizaldi; Jabang Nurdin (Jurnal Biologi Universitas Andalas, 2019)
A study on social network based on grooming interactions among males of long-tailed macaques (Macaca fascicularis) at Gunung Meru, Padang has been conducted from August to October 2015. The dominance relationship determined by submissive interactions among 17 adult males. Submissive interactions were recorded using ad libitum observation and grooming interactions by continuous recording method. The results showed that the dominance hierarchy among males was linear (Matman linearity index: h' = 0.97). Alfa male appeared to have the highest centrality index among all the males. This study indicates that individuals attained higher dominance hierarchy tend to have higher degree of centrality.